Perancangan Alat Ukur Potensi Wisata Budaya Pada Kabupaten Rembang Menggunakan Metode SECI dan AHP - Amelia, Mia; Septiningrum, Lutfia; Rumanti, Augustina Asih (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2022)
Rembang Regency is not a tourist destination in districts or cities in Central Java because tourist visits to tourist objects in Rembang Regency are still relatively small when compared to other areas around Rembang Regency such as Demak Regency, Kudus Regency, and Semarang Regency. The potential for cultural tourism in Rembang Regency is still relatively small compared to natural and artificial tourism. So that the potential to be taken is the potential for cultural tourism. There are six components of tourism development as the basis for research: Attraction, Amenities, Ancillary Service, Activity, Accessibility, and Accommodation. There are additional tourism development components from interviews with the Culture and Tourism Office of Rembang Regency, namely Environment and Human Resources. So that it can be managed clearly and accurately measured and tourism potential can be said to be feasible, it must first design indicators so that tourism managers can find out what must be developed for cultural tourism potential, so that later it is expected to become a tourist destination that can help the economy in the Regency Rembang. This study uses the SECI method (Socialization, Externalization, Combination, and Internalization). After getting the indicator then, calculate the weight using AHP (Analytical Hierarchy Process)